A new approach to improve the surface properties of H13 steel for metal forming applications by applying the TiAlN multi-layer coating. (April 2018) - Elmkhah, H.; Mahboubi, F.; Abdollah-zadeh, A.; Rouhaghdam, A.R. Sabour
Highlights: Ti(2) N layer as upper layer of TiAlN improves the tribological properties. Hardness value of TiN/TiAlN/Ti(2) N is slightly better than TiAlN single-layer. Adhesion and wear resistance of TiAlN enhance with companionship of TiN layer. Abstract: This work is an attempt to improve the mechanical and tribological properties of nanostructured TiAlN coatings through the plasma nitriding/TiN/TiAlN/Ti(2) N process for metal forming applictions. The coatings were deposited using the pulsed DC plasma-assisted chemical vapor deposition (PACVD) method at the constant working conditions including the frequency of 10 kHz, the deposition temperature of 470 °C, and the duty cycle of 33%. H2, Ar, and N2 gases and TiCl4 and AlCl3 precursors were fed to the chamber as the depositing agents. The results indicated that the three-layered coatings (TiN/TiAlN/Ti(2) N) have the enhaced adhesion strength and wear resistance than the single-layered ones (TiN or TiAlN). This is also showed that the surface morphology, grain size, and friction coefficient of the TiN coating are respectively smoother, smaller, and lower than those of the TiAlN coating. Accordingly, it was concluded that the Ti(2) N coating as a top coat is an appropriate material to improve the tribological and mechanical properties of nanostructured TiAlN coatings.